2023
DOI: 10.3390/healthcare12010079
|View full text |Cite
|
Sign up to set email alerts
|

Quiet Quitting among Nurses Increases Their Turnover Intention: Evidence from Greece in the Post-COVID-19 Era

Petros Galanis,
Ioannis Moisoglou,
Maria Malliarou
et al.

Abstract: As turnover intention is a strong determinant of actual turnover behavior, scholars should identify the determinants of turnover intention. In this context, the aim of this study was to assess the effect of quiet quitting on nurses’ turnover intentions. Additionally, this study examined the impact of several demographic and job characteristics on turnover intention. A cross-sectional study with 629 nurses in Greece was conducted. The data were collected in September 2023. Quiet quitting was measured with the “… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
(63 reference statements)
0
4
0
Order By: Relevance
“…Bullying is a factor that triggers the occurrence of quiet quitting in nurses [64] . However, quiet quitting does not seem to be enough to stop turnover either, as those who choose it are more likely to experience turnover [35] .…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Bullying is a factor that triggers the occurrence of quiet quitting in nurses [64] . However, quiet quitting does not seem to be enough to stop turnover either, as those who choose it are more likely to experience turnover [35] .…”
Section: Discussionmentioning
confidence: 97%
“…Both prior to and during the pandemic, the prevalence of turnover intention of nurses remained very high, exceeding 40% [32] , [33] , which is higher than for other health professionals [34] . The end of the pandemic also finds a large percentage of nurses (>40%) declaring their turnover intention [35] . Several organizational factors, such as reduced organizational support and understaffing, create the conditions for nurses' turnover intention [36] [39] .…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, emotional intelligence and moral resilience decrease the chance of this behavior [27,28]. Nurses who opt for quiet quitting are more inclined to express their turnover intention from their position [29]. The choice of quiet quitting by nurses is a work behavior that can be a barrier to innovation and efficiency in an organisation, as these employees have no commitment to the organisation, their thoughts are on leaving their job, and they do not show willingness to go beyond their job.…”
Section: Introductionmentioning
confidence: 99%
“…Quiet quitting has already been recognized as a significant threat for healthcare organizations, since the healthcare professionals may reduce their efforts to avoid job burnout, physical and mental outcomes, and occupational stress [22] , [24] . Moreover, a recent study highlighted the negative consequences of quiet quitting for healthcare professionals and organizations as scholars found that quiet quitting increased turnover intention among nurses [25] .…”
Section: Introductionmentioning
confidence: 99%